Sixteen Years of DNA Barcoding in China: What Has Been Done? What Can Be Done? - Yang, Cai-qing; Lv, Qing; Zhang, Ai-bing (Frontiers in Ecology and Evolution, 2020)
Over the past 16 years, more than half (59.68%) of research papers in China on DNA barcoding have been published in Chinese rather than English. Using the records in BOLD (Barcode of Life Data) system, we found Chinese scientists have contributed nearly 120 thousand DNA barcodes for more than 16 thousand species as of September, 2019, with barcoded species distributed throughout China. Based on 2,624 articles and 494 dissertations published during the last 16 years, we reviewed the basic statistics of these studies, including the type of articles contributed by Chinese scientists, the preference of taxonomic groups, the characteristic of barcoding studies in China, the current limitations, and potential future directions as well. We found that most barcode data pertain primarily to plants and animals. Most work in China has focused on verification of the authenticity of species used in traditional Chinese medicine, while other applications paid more attention to food safety, inspection and quarantine, and control of pests and invasive species. In methodology and technology, a number of new DNA barcoding methods were developed by Chinese scientists. However, there are several severe limitations of research on DNA barcoding in China in general, such as the lack of leadership in pioneering international projects, the absence of an open bioinformatics infrastructure, and the fact that some Chinese journals do not clearly require data transparency and availability for DNA barcodes, impeding the further development of barcode libraries and research in China. In the future, Chinese scientists should build authoritative online libraries, while aiming for theoretical innovations for both concepts and methodology of DNA barcoding.